Implementation of Learning Media Use in Improving the Quality of Learning at Tadika Suriah EduKids Centre Malaysia - Isman Efendi Limbong; Nadya Dwi Haryuni (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the implementation of learning media use in improving the quality of learning at Tadika Suriah EduKids Centre Malaysia. The research employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The research subjects consist of teachers and early childhood students. The findings reveal that the use of learning media, including visual, audio, and audiovisual media, enhances student engagement, facilitates understanding of learning materials, and creates a more interactive and enjoyable learning environment. In addition, teachers play a crucial role in selecting and managing appropriate media based on students’ characteristics. The challenges identified include limited facilities and varying levels of teachers’ competence in developing learning media. Therefore, professional training and development for teachers are necessary to optimize the implementation of learning media.